Anterograde trans-neuronal labeling of striatal interneurons in relation to dopamine neurons in the substantia nigra pars compacta - Karube, Fuyuki; Yang, Yang; Kobayashi, Kenta; Fujiyama, Fumino (Frontiers in Neuroanatomy, 2024)
Recent advances in neural tracing have unveiled numerous neural circuits characterized by brain region and cell type specificity, illuminating the underpinnings of specific functions and behaviors. Adeno-associated virus serotype 1 (AAV1) has emerged as a potent anatomical instrument capable of labeling and visualizing pre-and post-synaptic neurons simultaneously through anterograde transsynaptic labeling. Dopaminergic (DA) neurons in the midbrain are highly heterogeneous in terms of gene and protein expression and axonal projections. Different cell types within the substantia nigra pars compacta (SNc) tend to project to the striatum in a cell-type-dependent manner characterized by specific topography. Given the wide and dense distribution of DA axons, coupled with a combination of synaptic and volume transmission, it remains unclear how DA release is spatially and temporally, to appropriately achieve adapt to specific behaviors and functions. Our hypothesis posits that hidden rules governing synapse formation between pre-synaptic DA neuron types and striatal neuron types may modulate the effect of DA at a single-cell level. To address this conjecture, we employed AAV1 to visualize the neural circuitry of DA neurons. First, AAV1-Cre was injected into the SNc, resulting in Cre expression in both medium spiny neurons and interneurons in the striatum. Due to the potential occurrence of the retrograde transfer of AAV1, only striatal interneurons were considered for trans-synaptic or inter-neuronal labeling. Interneuron types expressing parvalbumin, choline acetyltransferase, somatostatin, or nitrogen oxide synthase exhibited Cre expression. Using a combination of AAV1-Cre and Cre-driven fluorophore expressing AAVs, striatal interneurons and the axons originating from the SNc were visualized in distinct colors. Using immunofluorescence against neurotransmitter transporters, almost all axons in the striatum visualized using this approach were confirmed to be dopaminergic. Moreover, individual DA axons established multiple appositions on the somata and proximal dendrites of interneurons. This finding suggests that irrespective of the extensive and widespread axonal arborization of DA neurons, a particular DA neuron may exert a significant influence on specific interneurons. Thus, AAV1-based labeling of the DA system can be a valuable tool to uncover the concealed rules governing these intricate relationships.